Thyroid fine needle aspiration biopsy: Do we really need an on-site cytopathologist? - TÜRELİ, DERYA; BUĞDAYCI, ONUR (ELSEVIER IRELAND LTD, 2014)
Purpose: The aim of this single center study is to evaluate the effectiveness of performing ultrasound-guided thyroid fine-needle aspiration biopsies (FNAB) performed by the radiologist alone without an on-site cytopathologist. Materials and methods: In this prospective randomized study, 203 patients with single nodules measuring 10 mm or more underwent ultrasound-guided FNAB: 102 patients underwent FNAB performed by the radiologist accompanied by a cytopathologist (control group); 101 patients underwent FNAB by the radiologist alone (study group). In both groups biopsy time, specimen adequacy ratio, total aspiration number, cytopathologist's cytological diagnosis time (t1), cytopathologist's total time consumption (t2) were evaluated. Results: Mean total biopsy time was 8.74 +/- 2.31 min in the study group and was significantly shorter than the control group's 11.97 +/- 6.75 min (p = 0.004). The average number of aspirations per patient in the study group was 4.00 +/- 0; compared to the control group's 3.56 +/- 1.23 this was significantly higher (p = 0.001). t1 of the study group was 307.48 +/- 226.32 s; compared to 350.14 +/- 247.64 s in the control group, there was no statistically significant difference (p = 0.137). t2 of the study group was 672.93 +/- 270.45 s; compared to the control group (707.03 perpendicular to 258.78 s) there was no statistically significant difference (p = 0.360). Diagnostic adequacy of aspirated specimens was reassessed in the pathology laboratory. In the study group, 84 out of 101 aspirations and in the control group 89 out of 102 aspirations was determined as adequate with no statistically significant difference (p = 0.302). Conclusions: We believe that in centers where a cytopathologist is not available, ultrasound-guided thyroid FNAB can be adequately performed by an experienced radiologist who was effectively trained in smear preparation. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Thyroid nodule; Fine needle aspiration biopsy; Specimen adequacy; Image-guided intervention; NODULES; MANAGEMENT; DIAGNOSIS; CANCER